فساد الزمان وأثره في الفتاوى والأحكام - طاهري, بلخير (جامعة الوادي - University of Eloued, 2021)
الفقه الإسلامي وليد الحركة في المجتمع، ويِّجد للناس على قدر تحركهم وسعيهم من مستجدات يتتطلبها الواقع المعاش، ويحدث للناس من مسائل على قدر زمانهم، ولكن أحيانا ضغط الواقع لا يجري على وفق سنن التشريع، فيدخل المكلف في حرج مما يدفعه دفعا إلى إرتكاب محظور وتجاوز مشروع، مما يجعل المسألة بين ضغط الواقع و مراد الشارع، و تنزيل الفقيه، و أحيانا بعض الفتاوى يكون فيها إكراها على غير المعتاد، مما يجعل البعض يتنصل عن ضوابط الشرع لإرضاء المكلف، أو السلطان، وهنا يستلزم أن توضع قيودا صارمة حتى لا يتفلت الحكم وتذهب هيبة الشريعة. Islamic jurisprudence is the product of movement in society, and it finds for people according to their movement and their pursuit of developments that are required by the lived reality, and it occurs to people from issues according to their time, but sometimes the pressure of reality does not take place in accordance with the laws of legislation, so the taxpayer gets into embarrassment, which pushes him to commit a prohibited and bypass a project. , which makes the issue between the pressure of reality and the desire of the legislator, and downloading the jurist, and sometimes some fatwas are coercion on the unusual, which makes some renounce the controls of the law to satisfy the taxpayer, or the sultan, and here it is necessary to put strict restrictions so that the ruling does not escape and go Sharia prestige.
مقال
Keywords: فساد؛ الزمان؛ الفتوى؛ الاجتهاد؛ الأحكام؛ الفقه؛ المعاملات؛ النصوص.